Cardiac resynchronization therapy pacemaker or cardiac resynchronization therapy defibrillator: what determines the choice?—findings from the ESC CRT Survey II. Issue 6 (13th February 2019) - Normand, Camilla; Linde, Cecilia; Bogale, Nigussie; Blomström-Lundqvist, Carina; Auricchio, Angelo; Stellbrink, Christoph; Witte, Klaus K; Mullens, Wilfried; Sticherling, Christian; Marinskis, Germanas; Sciaraffia, Elena; Papiashvili, Giorgi; et al.
Abstract: Aims: The decision to implant a cardiac resynchronization therapy pacemaker (CRT-P) or a cardiac resynchronization therapy defibrillator (CRT-D) may be challenging. There are no clear guideline recommendations as no randomized study of cardiac resynchronization therapy (CRT) has been designed to compare the effects of CRT-P with those of CRT-D on patients' outcomes. In the CRT Survey II, we studied patient and implantation centre characteristics associated with the choice of CRT-P vs. CRT-D. Methods and results: Clinical practice data from 10 692 patients undergoing CRT implantation of whom 7467 (70%) patients received a CRT-D and 3225 (30%) received a CRT-P across 42 ESC countries were collected and analysed between October 2015 and January 2017. Factors favouring the selection of CRT-P implantation included age >75 years, female gender, non-ischaemic heart failure (HF) aetiology, New York Heart Association functional Class III/IV symptoms, left ventricular ejection fraction >25%, atrial fibrillation, atrioventricular (AV) block II/III, and implantation in a university hospital. Conclusion: In a large cohort from the CRT Survey II, we found that patients allocated to receive CRT-P exhibited particular phenotypes with more symptomatic HF, more frequent comorbidities, advanced age, female gender, non-ischaemic HF aetiology, atrial fibrillation, and evidence of AV block. There were substantial differences in the proportion of patients allocated to receive CRT-P vs. CRT-D between countries.